Helicobacter spp. and gastric lesions association in minipigs - Renato Luiz Silveira; Ana Claudia de Menezes Cruz; Hassan Jerdy Leandro; Mariah Bianchi Reis Gusmão Petronilha; Rachel Bittencourt Ribeiro Rodrigues; Maria Aparecida da Silva; Raphael Mansur Medina; Fabiana Batalha Knackfuss; Eulógio Carlos Queiroz de Carvalho (Ciência Rural, 2021)
ABSTRACT: Due to their similarity to humans, studies regarding gastric ulcers in pigs have become of great interest. It is known that Helicobacter spp. is related to the occurrence of these ulcers, as they possess a high prevalence in pigs. This study aimed to associate gastric lesions findings naturally occurring in minipigs related to or not related to the presence of Helicobacter spp., through the ultra-rapid urease test and immunohistochemical analysis, reaffirming the disease in swine as a natural biomedical model for human cases. For this, samples of formalin-fixed paraffin-embedded gastric tissues from 40 minipigs were obtained at the Laboratório de Morfologia e Patologia Animal (LMPA) in the Universidade Estadual do Norte Fluminense (UENF). Regarding the ultra-rapid urease test, no animal was positive in all regions. However, 18 were positive in at least one: six (15%) were positive in the aglandular region, eight (20%) in the antrum region, 13 (32.5%) in the region of the cardiac gland, and one (2.5%) in the region of the fundic gland. Regarding immunohistochemical analysis, only one animal was positive in all regions, and 32 animals were positive in at least one: four (10%) were positive in the aglandular region, 10 (25%) in the antrum region, 23 (57.5%) in the region of the cardiac gland, and three (7.5%) in the region of the fundic gland. The gastric lesion findings showed a close relationship with Helicobacter spp., enriching the laboratory animal pathologies list. The immunostaining of the bacteria not associated with gastric lesions in certain regions demonstrated the saprophytic and opportunisitic nature of Helicobacter.